Ibn Ashur's Concept of Maqasid Sharia-Finding Method - Ade Dedi Rohayana; Muhammad Jauhari Sofi; Irfandi Irfandi (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2020)
This paper aims to reveal the concept of maqasid sharia-finding method according to Tahir ibn Ashur. It argues that Ibn Ashur’s approach to search for maqasid sharia revolves around three methods. The first is inductive method. This method can be done through the induction of many ‘illat (reasons) that have the same hikmah (goals) and the induction of many dalil (provisions) that have the same ‘illat (reasons). The second is al-bayan al-nashshi method. This method refers to understanding of explicit provisions (dalil) in the Qur'an as they leave no room for alternative interpretations according to Arabic language traditions. The third is sunnah mutawatirah method. This method is divided into mutawatir ma’nawi and mutawatir 'amali. Mutawatir ma'nawi is an inference resulted from testimonies of many shahaba (the Prophet's companions) concerning a Prophet's particular action. Actions that are considered mutawatir ma'nawi include those that are clear, bright and axiomatic in nature (ma'lum min al-din bi al-dharurah), or at least close to ma'lum min al-din bi al-dharurah. Meanwhile, mutawatir ‘amali is an inference resulted from a testimony of one shahaba concerning actions always repeated by the Prophet.